PEMANFAATAN MEDIA PEMBELAJARAN (AUDIO-VISUAL) DALAM MATA PELAJARAN SOSIOLOGI BERDASARKAN TEORI BELAJAR BEHAVIORISTIK PADA PESERTA DIDIK DI SMA NEGERI 2 KOTA SERANG - Fhabella, Anten; Kuntari, Septi (Universitas Tanjungpura, 2022)
The aim to be accomplished in writing this article is 1). To find out how audio-visual learning media is practiced in Sociology subjects based on behavioristic theories of behaviorists, 2). To know how learners' behavior changes make use of the learning media during the learning process in the classroom. 3). To see if learners are becoming more interested in Sociology materials or otherwise. The study uses qualitative descriptive research methods and observations with a class action research model and interviews in-depth learners to supplement the study data needs. The subject of this study is a 10-grade learner of the social science program at SMAN 2 Serang city. The result of this study was that learners who learned by using the audio-visual medium tended to change their behavior better in processing the Sociology subject taught by the teacher in the class. To demonstrate such conduct requires repetition in utilizing the medium of study in Sociology subjects.